Examining the Effects of Detraining and Retraining on Health Outcomes in Community Fitness Program. - Grotthus, Jenna L. (My University, 2009)
The primary purpose of this study was to determine if not participating in a regular community fitness program (CFP) during the summer months (12-wk) negatively impacts health (detraining). The secondary purpose was to determine if potential decreases in health for participants not exercising during the summer months could be regained after resuming fall CFP (retraining).
Color poster with text and graphs describing research conducted by Jenna L. Grotthus, advised by Lance C. Dalleck.
Keywords: Exercise--Health aspects; Exercise--Physiological aspects; Physical education and training; Physical fitness--Physiological aspects; Physical fitness--Testing; Posters